La figura di Louise de Coligny nell'opera di Eliana Bouchard - Artico, Davide (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The starting point of this paper is Eliana Bouchard’s novel Louise. Canzone senza pause. The article presents a brief analysis of its contents and of the formal literary solutions adopted. A few references to other authors are also provided for the purpose of placing Bouchard’s work in the mainframe of late 20th century female writers who were either linked with the Italian region of Piedmont or produced historical fiction. Thence, an attempt is made to heuristically separate the plan of formal appurtenance to a literary genre from the plan of axiology, that is, of the ideological, moral, and religious values which the author tries to convey by means of her imaginative writing, given her own metatextual statements in interviews about the book. As a result, a discrete line is drawn separating the rather conservative formal criteria according to which, in today’s Italian literature, a novel may be deemed to belong in the sub-genre of historical narrative, from the novelty represented by contamination with other categories of non-academic writing, such as feminist selfconscience literature and Christian apologetics typical of Calvinist denominations. A shift is also recorded in contemporary identity milestones compared to those implicitly present in 19th century historical fiction. While 19th century historical novels conveyed the ideals of territorial appurtenance and social formalisation of feelings within the institution of marriage, in Bouchard’s novel an over-national identity trait is proposed, according to which an individual belongs in a (denominational) community based on her own free will, and not by birthright, whereas women’s social role is made independent from such male characters as father or husband
Keywords: hugenots; contemporary italian literature; historical literatur; ugonotti; romanzo storico; letteratura italiana contemporanea